Biosorption of zinc (II) from aqueous solution by using dried water hyacinth (Eichhornia crassipes) - Siti Aminah, Sharif Babu (2009)
This paper shows a detailed study to investigate the potential of water hyacinth as biosorbent, to remove Zinc (II) from aqueous solution and to identify the optimum condition for the parameter involved. Before the biosorption experiment was done, the water hyacinth was first collected at Lake in Pekan, Pahang. Then the water hyacinth was washed to remove dirt and was chopped to separate the aerial and root part. Finally, the water hyacinth was dried before it was blended into a smaller particles size. There were four parameter that have been studied in this paper, they were effect of biosorbent dosage, effect of initial concentration, effect of pH and effect of time contact. It was found that the optimum dosage for the biosorbent at initial metal concentration of 10 mg/L was 0.2 g; the optimum pH was at 5.4 and the optimum time contact was at 90 minutes for initial concentration 5 mg/L and 210 minutes for initial concentration 10 mg/L. At the optimum condition the removal of zinc was increased as the initial concentration was increased. The biosorption of zinc was occurred at pH acidic because the pH dependence of metal uptake could be related to functional group of the biomass and also to solution chemistry. The result proved that the water hyacinth was a good biosorbent to remove zinc from waste water and biosorption can be used to replace the conventional treatment methods because it was low cost, high efficiency of metal removal from dilute solutions and also applicable for industrial.